Numerical characterization of compact pipe specimen for stretch zone width assessment. Issue 7 (4th February 2016) - Mahajan, G.; Saxena, S.; Mohanty, A.
Abstract: Present work focuses on evaluating the suitability of newly proposed compact pipe (CP) fracture specimen geometry for determining critical SZW. The effect of varying the parameter of CP specimen (outer diameter, thickness, a/W ratio and straight and radial crack front) on critical SZW have been studied. It is found that SZWc values decreases slightly with the increase in outer diameter of CP specimen. In CP specimen, thickness greater than a specified value is to be used for geometry independent evaluation of SZWc. Critical SZW shows significant variation with a/W ratio, straight and radial crack front. The CP specimen and Three Point Bend (TPB) specimen also compared in terms of stress tri‐axiality.